ATURAN PENJUMLAHAN DAN PERKALIAN DALAM KAIDAH PENCACAHAN: BAGAIMANAKAH DESAIN HYPOTHETICAL LEARNING TRAJECTORY BERBASIS RME? - Laela Nur Rokhmawati; Nani Ratnaningsih; Khomsatun Ni'mah (IKIP Siliwangi, 2023)
This study aims to design HLT addition and multiplication rules in the RME-based enumeration rules and implement the HLT design in learning activities. The research method used in this research is design research. This research was conducted at SMA Negeri 2 Banjar in the even semester of the 2022-2023 school year, the research subjects in the teaching experiment were 35 students of class XII.IPA4 and then in the pilot experiment there were 36 students of class XII.IPA1. Data collection techniques in the form of observation, interviews, and video recording. In this study the designed HLT was compared with actualization in the learning process. This research produced a learning trajectory for addition and multiplication rules in the enumeration rules which were obtained through learning activities using the Realistic Mathematical Education (RME) approach.